Urgensi Pengundangan Rancangan Undang-Undang Masyarakat Hukum Adat sebagai Bentuk Kesetaraan Warga Negara - Saswoyo, Ade Bagus; Pura, Margo Hadi (Universitas Negeri Surabaya, 2023)
Indonesia is a country that has a diversity of ethnicities, races, religions and languages, including the existence of indigenous and tribal peoples. In fact, there is injustice that is felt by a number of indigenous peoples in the form of a lack of protection and recognition by the state for the existence of indigenous and tribal peoples, such as the Kuningan Regency Government's decision not to recognize the application of the Sunda Wiwitan community as indigenous peoples (MHA). The refusal was based on a letter from the Regent of Kuningan Number 189/3436/DPMD on December 29 2020. The reason was that Sunda Wiwitan was deemed not to comply with Minister of Home Affairs Regulation Number 52 of 2014 regarding the recognition of MHA, namely history, customary territories, customary law, assets and/or customary objects, as well as institutions/customary governance systems. This study aims to analyze the urgency of the importance of passing the Indigenous Peoples Law to facilitate various indigenous and tribal peoples in Indonesia. This study uses a normative juridical research method with a conceptual and statutory approach. The Bill on Customary Law Communities has actually been included in the National Legislation Program and has reached the harmonization stage and needs to add substance regarding the regulation of customary law community areas so that indigenous peoples live safely, grow and develop as a community group in accordance with their human dignity. The urgency of ratifying the Bill on Customary Law Communities is needed to ensure that indigenous and tribal peoples are free from discrimination, including reducing conflicts that often occur over ownership of customary/forest territories so that Indigenous Peoples' position as citizens is equal to other citizens in Indonesia.